1480. Incidence of Non-Invasive Pneumococcal Pneumonia in Children in the United States before and after Introduction Pneumococcal Conjugate Vaccines (PCV7 and PCV13) during 1998-2018. (31st December 2020) - Hu, Tianyan; Sarpong, Eric; Song, Yan; Done, Nicolae; liu, Qing; Signorovitch, James; Petigara, Tanaz
Abstract: Background: Pneumonia causes significant pediatric morbidity, mortality, and healthcare resource utilization . S. pneumoniae is a leading cause of bacterial pneumonia in children. Merck is developing V114, an investigational 15-valent PCV that contains PCV13 serotypes as well as 22F and 33F. To demonstrate the potential value of V114, it is important to estimate the remaining burden associated with pneumococcal pneumonia (PP). This study was to estimate incidence rates (IRs) of non-invasive PP before and after PCV7 and PCV13 introduction in children in the US. Methods: PP-related claims in children < 18 years were identified in the IBM MarketScan ® Commercial database (1998-2018) using pneumococcal specific ICD9/10 codes. Claims with any invasive pneumococcal disease ICD9/10 codes were excluded. An episode could comprise one or more claims. Episodes with any inpatient stays were categorized as inpatient, and as outpatient otherwise. Age-stratified (< 2, 2-4, and 5-17 years) IRs were episodes per 100, 000 patient-years (PYs) during the pre-PCV7 (1998-1999), early and late PCV7 (2001-2005, 2006-2009), and early and late PCV13 (2011-2013, 2014-2018) periods. Results: Inpatient and outpatient PP IRs decreased steadily in children < 2 years (146.8, 117.9, 102.0, 67.8, and 32.2 per 100, 000 PYs for pre-PCV7, early and late PCV7, and early and late PCV13 periods, respectively; Figure 1 ). In children 2-4 years, IRs increased slightly from 88.6 to 90.0 per 100, 000 PYs from the pre-PCV7 to early PCV7 period, then declined to 83.9 and 30.8 per 100, 000 PYs in the late PCV7 and late PCV13 periods, respectively (Figure 2) . In children 5-17 years, IRs declined from 35.3 to 34.2 per 100, 000 PYs from the pre-PCV7 to early PCV7 period, stabilized at 34.1 per 100, 000 PYs in the late PCV7 period, followed by a steeper decline to 12.5 per 100, 000 PYs in the late PCV13 period (Figure 3) . The majority of episodes were outpatient in all three age groups. Figure 1. Non-invasive pneumococcal pneumonia incidence in children <2 years, episodes per 100, 000 patient-years (1998 - 2018) Figure 2. Non-invasive pneumococcal pneumonia incidence in children 2 - 4 years, episodes per 100, 000 patient-years (1998 - 2018) Figure 3. Non-invasive pneumococcal pneumonia incidence in children 5 - 17 years, episodes per 100, 000 patient-years (1998 - 2018) Conclusion: In children < 2 years, IRs of non-invasive PP decreased after introduction of PCV7 and PCV13. Following introduction of PCV 7 and PCV13, there remains a residual burden of non-invasive PP in children in the US. The impact of future PCVs on PP will depend on the proportion of PP caused by S. pneumoniae and vaccine-type serotypes. Disclosures: Tianyan Hu, PhD, Merck (Employee, Shareholder) Yan Song, PhD, Merck (Consultant) Nicolae Done, PhD, Merck & Co., Inc. (Consultant) Qing liu, PhD, Merck (Consultant) James Signorovitch, PhD, Merck & Co., Inc. (Consultant) Tanaz Petigara, PhD, Merck & Co., Inc. (Employee, Shareholder)